An in-vitro study on the anti-microbial properties of alum versus streptococcus mutans and its effectiveness in different concentrations of 5%, 10%, 15%, 20% and 25% - Del Valle, Ferdinand
Commercially available alum or "tawas" as it is commonly known, was tested for its anti-microbial properties against Streptococcus mutans, a microorganism implicated in the etiology of dental caries. The purpose of this paper was to determine if: 1.) alum had significant anti-bacterial activity against S. mutans; and, 2.) to compare the effectiveness between 5, 10, 15, 20 and 25% solutions of alum against the said microorganism. The results of the experiment show that alum does have significant anti-microbial action against s. mutans. Furthermore, there are significant differences in the anti-microbial actions of 5%-25% solutions of alum. There is a steady increase in the zone of inhibition of the microorganism brought about by the increase in concentration up to 20%. Thereafter, there is no longer any significant difference in the anti-microbial activity.